2010
DOI: 10.1063/1.3505763
|View full text |Cite
|
Sign up to set email alerts
|

Ionic properties of liquid crystals dispersed with carbon nanotubes and montmorillonite nanoplatelets

Abstract: The ionic properties of liquid crystals doped with one-dimensional carbon nanotubes, two-dimensional montmorillonite, and a mixture of both are investigated. The results indicate that the relaxation times of electrode polarization and ionic conductivity are time-dependent after the cell fabrication regardless of doping. While all of the dopants are effective in capturing impurity ions, the cells containing the hybrid dopant exhibit the feeblest ionic effect at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…1,2 Moreover, investigations demonstrating the suppressed ionic effect by nanodopants have also been clarified for solving image problems in LC displays caused by ubiquitous impurity ions. [3][4][5][6][7] Depending on the intrinsic characteristics of the dopant and mutual interaction with LC molecules, researchers have studied the individual effects of nanomaterial additives on the behaviors of phase transitions in LCs in terms of the molecular ordering, 8,9 dielectric relaxation, 10 and electrophysical properties of LCs. [11][12][13] Among currently available nanomaterials, graphene, classified as a two-dimensional (2-D) carbon allotrope, has attracted immense attention for potential applications in electronic devices and nanocomposites since its successful isolation in 2004.…”
mentioning
confidence: 99%
“…1,2 Moreover, investigations demonstrating the suppressed ionic effect by nanodopants have also been clarified for solving image problems in LC displays caused by ubiquitous impurity ions. [3][4][5][6][7] Depending on the intrinsic characteristics of the dopant and mutual interaction with LC molecules, researchers have studied the individual effects of nanomaterial additives on the behaviors of phase transitions in LCs in terms of the molecular ordering, 8,9 dielectric relaxation, 10 and electrophysical properties of LCs. [11][12][13] Among currently available nanomaterials, graphene, classified as a two-dimensional (2-D) carbon allotrope, has attracted immense attention for potential applications in electronic devices and nanocomposites since its successful isolation in 2004.…”
mentioning
confidence: 99%
“…It was also observed that the efficiency to trap ions by nano-clay was varying in time [213]. More efficient ion trapping in liquid crystals can be achieved by combining low concentrations of nano-clay with comparable amounts of carbon nanotubes [214]. Higher concentrations of montmorillonite in nematic liquid crystals (up to 5 wt.…”
Section: Flcmentioning
confidence: 97%
“…Conducting nanofiber NLC Increase in the conductivity [208,209] Polymeric nanoparticles FLC Decrease in dielectric losses [210] Nanoclay (montmorillonite) NLC Ion trapping, time dependent properties, and aggregation [211][212][213][214][215][216][217] x x S ZnO …”
Section: Refmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu and W. Lee have studied temperature dependent dielectric properties of MMT and CNT doped nematic LC E7. They have concluded that, dopant does not influence the intrinsic identity of LC host in terms of dielectric dispersion till the clearing temperature of nematic LC [30]. But at the higher temperature, thermal agitation becomes more predominant as compared to intermolecular interaction which produces randomization of dipoles [17,31].…”
Section: Dielectric Responsementioning
confidence: 99%